lncRNA RMST Suppressed GBM Cell Mitophagy through Enhancing FUS SUMOylation - Changhong Liu; Zixuan Peng; Peiyao Li; Haijuan Fu; Jianbo Feng; Yan Zhang; Tao Liu; Yang Liu; Qing Liu; Qiang Liu; Di Li; Minghua Wu (Elsevier, 2020)
Long non-coding RNAs (lncRNAs) play a significant role in post-translational modifications of proteins, yet the importance of lncRNAs for SUMOylation is unknown. rhabdomyosarcoma 2 associated transcript (RMST) expression in glioma tissues and normal brain tissues was measured by quantitative real-time PCR and in situ hybridization. The functional roles of RMST in astrocytomas were demonstrated by a series of in vitro experiments. The potential mechanisms of RMST for SUMOylation were investigated by RNA immunoprecipitation, RNA pull-down, western blotting, and coimmunoprecipitation assays. We first demonstrated the oncogenic activity of lncRNA RMST by inhibiting glioma cells mitophagy. We also first determined that RMST is an enhancer of FUS SUMOylation, especially boosting SUMO1 modification at K333. SUMOylation induced by RMST contributes to the interaction between FUS and heterogeneous nuclear ribonucleoprotein D (hnRNPD) and stabilized their expression and cells mitophagy. Importantly, lncRNA RMST could serve as a promising prognostic factor for glioma patients. Our results demonstrated a previously unknown function of lncRNAs worked as an enhancer in FUS SUMOylation, and RMST will be a significant guide for the development of medications targeting gliomas. Keywords: lncRNA, SUMOylation, oncogene, GBM